2017
DOI: 10.25125/agriculture-journal-ijoear-nov-2017-11
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of plant growth promoting bacteria (PGPB) from anaerobic digestate and their effect on common wheat (Triticum aestivum) seedling growth

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In this context, our results reinforce previous data indicating that psychrophilic AD is an efficient and viable process [61] to produce biogas with high methane content. The resulted digestate presented an absence or reduced load of potential microbial pathogens [50] and with the potential to harbor plant growth-promoting bacteria [62], which can benefit agricultural crops [63]. However, the feasibility of applying the digestate resulting of anaerobic digestion as a safe fertilizer for plants in large-scale agriculture still needs to be verified.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, our results reinforce previous data indicating that psychrophilic AD is an efficient and viable process [61] to produce biogas with high methane content. The resulted digestate presented an absence or reduced load of potential microbial pathogens [50] and with the potential to harbor plant growth-promoting bacteria [62], which can benefit agricultural crops [63]. However, the feasibility of applying the digestate resulting of anaerobic digestion as a safe fertilizer for plants in large-scale agriculture still needs to be verified.…”
Section: Discussionmentioning
confidence: 99%
“…Indirectly, digestates may affect plant growth through modifications of the physical, chemical, and biological properties of the soil, for example, enhanced soil water holding capacity and CEC and improved soil structure (Stevenson, 1994). In addition, recent studies have identified beneficial microbes in digestates, such as plant growth promoting bacteria (PGPB) (Qi et al, 2017).…”
Section: Effects Of Msw Digestate On Plant Growthmentioning
confidence: 99%
“…Biosynthesis of IAA by Pseudomonas aeruginosa has been widely reported [59][60][61][62][63][64][65][66][67][68]; however, only a few studies have reported the production of GA3 by Pseudomonas aeruginosa [67][68][69]. Although cytokinin compounds have also been reported to be produced by Pseudomonas aeruginosa, there are quite a few reports on the biosynthesis of zeatin, and kinetin by this bacterial genus [68,[70][71][72].…”
Section: Assessment Of the Potential Biocontrol Of Robusta Coffee Nematodes And Plant-promoting Effect Of Pseudomonas Aeruginosa Tun03 Unmentioning
confidence: 99%